2007
DOI: 10.2147/ce.s7432
|View full text |Cite
|
Sign up to set email alerts
|

Adalimumab in ankylosing spondylitis: an evidence-based review of its place in therapy

Abstract: Introduction: Ankylosing spondylitis (AS) is an idiopathic chronic inflammatory disease that has prominent effects on the spine and peripheral joints. In addition, extraarticular manifestations such as enthesitis and acute anterior uveitis may be clinically important. In recent years, the therapy of AS has changed, largely due to the introduction of inhibitors of the proinflammatory cytokine tumor necrosis factor (TNF). Adalimumab, a human monoclonal antibody specifically for TNF, is the most recent of the TNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
(40 reference statements)
1
2
0
Order By: Relevance
“…Comparison of the e cacy of biosimilar adalimumab injection with iADA injection based on ASAS 20, ASAS40, ASAS70, ASAS5/6, BASDAI50 response criteria, and global assessment of disease activity scores showed that the ndings are similar to that demonstrated in landmark studies of adalimumab. [11][12][13] The study ndings are also comparable to the results reported for other adalimumab biosimilars. Based on the primary e cacy analysis with respect to subjects achieving ASAS20 response criteria at visit 5 (week 6) and 8 (week 12), it was observed that the lower limits of the 95% CI for treatment difference was within the non-inferiority margin (i.e., 20% set for the study).…”
Section: Discussionsupporting
confidence: 84%
“…Comparison of the e cacy of biosimilar adalimumab injection with iADA injection based on ASAS 20, ASAS40, ASAS70, ASAS5/6, BASDAI50 response criteria, and global assessment of disease activity scores showed that the ndings are similar to that demonstrated in landmark studies of adalimumab. [11][12][13] The study ndings are also comparable to the results reported for other adalimumab biosimilars. Based on the primary e cacy analysis with respect to subjects achieving ASAS20 response criteria at visit 5 (week 6) and 8 (week 12), it was observed that the lower limits of the 95% CI for treatment difference was within the non-inferiority margin (i.e., 20% set for the study).…”
Section: Discussionsupporting
confidence: 84%
“…All participants received subcutaneous injections of adalimumab (CinnoRA®, CinnaGen Co., Tehran, Iran) 40 mg/0.8 mL at the baseline and every 2 weeks during the study period. Adalimumab is an anti‐TNF medication with favorable effects in treating patients with AS 15,16 . In addition, patients in the control group (P) received a pamphlet covering information about AS and a set of illustrated exercises for managing AS.…”
Section: Methodsmentioning
confidence: 99%
“…Adalimumab is an anti-TNF medication with favorable effects in treating patients with AS. 15,16 In addition, patients in the control group (P) received a pamphlet covering information about AS and a set of illustrated exer-…”
Section: Study Interventions and Protocolsmentioning
confidence: 99%